Transfer of development rights and public facility planning in Taiwan: An examination of local adaptation and spatial impact - Shih, Mi; Chang, Hsiutzu Betty (Urban studies (Edinburgh, Scotland), 2016)
Since the early 2000s, transfer of development rights has served as a compensatory regime to address the ‘reserved land’ issue in Taiwan, a planning challenge that has seen private owners remain uncompensated for land flagged by the government for public facilities. This article investigates two aspects of the implementation of transfer of development rights in Taiwan. First, it examines the local adaptation process by which the use of transfer of development rights has been diverted from its original function of historical preservation. Second, it maps the spatial impact of this compensation process, using Sanchong District in New Taipei City as a case study. We demonstrate that trends of high-end developments in prime locations and ‘piecemeal transfer’ in the city’s older, inner neighbourhoods show worrisome patterns of uneven development. We conclude that the neoliberal effects generated by the transfer of development rights policy have complicated the planning challenge the policy was initially intended to resolve.